2011
DOI: 10.1080/15377857.2011.614548
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Dimensions of Mobilization: The Effect of Direct Contact and Political Ads on Latino Turnout in the 2000 Presidential Election

Abstract: Campaigns are not national, monolithic, one-size-fits-all events, but instead can be viewed as separate, segmented attempts to engage different groups of voters. This paper explores the effectiveness of different types of mobilization strategies among one group of voters, Latinos. Drawing from an integrated marketing communications framework, we argue that both direct contact and indirect contact should be effective in mobilizing Latinos, with the former having a stronger effect. In addition, we argue that tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In 2016, the Federal Communications Commission (FCC) reported that 133 SLTV stations served 39 media markets, and SLTV stations covered 79% of Latino households who own a television . The growth of these stations has coincided with the increasing importance of Latinos as a voting bloc, and political organizations have responded by producing group‐targeted campaign messages (Barreto ; Barreto, Merolla, and Soto ; Panagopoulos and Green ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, the Federal Communications Commission (FCC) reported that 133 SLTV stations served 39 media markets, and SLTV stations covered 79% of Latino households who own a television . The growth of these stations has coincided with the increasing importance of Latinos as a voting bloc, and political organizations have responded by producing group‐targeted campaign messages (Barreto ; Barreto, Merolla, and Soto ; Panagopoulos and Green ).…”
mentioning
confidence: 99%
“…Despite the growing prevalence of ethnic media (e.g., ethnic television), and evidence that short‐term exposure to group‐targeted foreign‐language campaign advertisements can foster electoral engagement (Barreto, Merolla, and Soto ), our knowledge of how long‐term access to ethnic media affects political behavior remains limited. Indeed, existing research on the political effects of ethnic media is characterized by competing theoretical expectations and inconsistent empirical results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other works have found that campaigns can have significant effects on Latino voter participation rates (e.g., Abrajano 2010: Barreto et al 2011;DeFrancesco Soto and Merolla 2006;García Bedolla and Michelson 2012;Panagopoulos and Green 2010). In light of this literature, it is reasonable to assume that Latino immigrants are cognizant of election-year political conflict and out-reach.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Both types of messages could be compelling for immigrants, making the American party system more approachable. Since the 1990s, campaign organizations have made special efforts to reach out to foreign-born Latinos by airing increasing numbers of political ads in Spanish (Abrajano 2010;Barreto, Merolla, and DeFrancesco Soto 2011).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%